STUDI DESKRIPTIF: PENGETAHUAN IBU USIA REMAJA DALAM PENGASUHAN BAYI USIA 0-6 BULAN DI WILAYAH KERJA PUSKESMAS OESAPA - miryam mur olla; Fepyani Thresna Feoh; Maria Yasintha Goa (STIKes CHMK, 2022)
Parenting is a structure of activities that carried out by parents in providing care (cleaning, protecting, providing food and maintenance). Maternal age is one of the main factors in providing optimal care for 0-6 month old babies. Sufficient knowledge is one of the main supporters for adolescent mothers in forming their actions in providing proper care. The purpose of this study is to describe the knowledge of adolescent mothers in take care of 0-6 month old babies. This research is conducted in the work area of Oesapa Health Center in October 2020. This research is a quantitative research with a descriptive design. Respondents in this study are 46 adolescent mothers with a total sampling technique. The instrument used is a questionnaire. The results showed that 12 people (26%) have enough knowledge, 36 adolescent mothers (74%) have less knowledge in caring 0-6 month old babies in the work area of Oesapa Health Center. Suggestion for health workers (nurses/midwifes) at the Oesapa Health Center is to reach all teenage mothers through health education related to the care of children in 0-6 month ages by involving the family. Keywords: Knowledge, Adolescent Mother, Parenting